Clinical trial participant information leaflets overstate the harms/risks of participation and understate the benefits - Rafaela Carapeto; Andrew Willis; Frances Shiely (PLoS ONE, 2026)
Objectives Participant Information Leaflets (PILs) are essential for informed consent in randomised controlled trials (RCTs), detailing the trial’s purpose, methods, and potential benefits and harms/risks to aid participant decision-making. The purpose of our study was to establish the balance of benefits and harms/risks communicated to trial participants in PILs. Study Design and Setting A retrospective study of 228 PILs from trials in the UK and Ireland. Benefits and harms/risks were defined and quantified through a systematic extraction and coding process. The analysis included the calculation of mean, median, and ranges for word counts of positive and negative reinforcement statements, and their proportional representation in the overall content of the PILs. Results The study included PILs from 26 Clinical Trial Units and Clinical Research Facilities, covering 228 unique studies in the UK and Ireland. The word count for positive reinforcement statements (median: 56 words, 2.3% of total PIL word count) was significantly lower than for negative reinforcement statements (median: 149 words, 5.7% of total PIL word count). Approximately 72% of PILs contained a higher percentage of words dedicated to negative rather than positive reinforcement, indicating an imbalance in presenting harms/risks over benefits. Conclusions The findings suggest that information in participant information leaflets places greater emphasis on potential harms and risks than on potential benefits of trial participation. While regulatory requirements necessitate clear communication of possible harms, the relatively limited emphasis on potential benefits may influence how participants interpret trial information. These findings highlight the importance of ensuring that participant-facing materials present both potential harms and benefits in a balanced and accessible way to support informed decision-making. Greater guidance for trial teams on how to present this information may help improve the clarity and balance of participant information leaflets.